Activation of RANKL‐induced osteoclasts and memory T lymphocytes by Porphyromonas gingivalis is serotype dependant. (May 2014) - Vernal, Rolando; Díaz‐Zúñiga, Jaime; Melgar‐Rodríguez, Samanta; Pujol, Myriam; Diaz‐Guerra, Eva; Silva, Augusto; Sanz, Mariano; Garcia‐Sanz, Jose A.
Abstract Aim Destructive periodontitis is associated with a Th1–Th17 immune response and activation of RANKL‐induced osteoclasts. In addition, Porphyromonas gingivalis K1 and K2 serotypes induce a strong Th1–Th17 response. This study aimed to investigate whether these P. gingivalis serotypes induce higher osteoclasts activation, by increased Th17‐associated RANKL production, and an antigen‐specific memory T‐lymphocyte response. Material and Methods The RANKL production and TRAP+ osteoclast induction were quantified on naïve T lymphocytes stimulated with dendritic cells primed with the P. gingivalis serotypes. The T‐bet, GATA‐3, RORC2 and Foxp3 expression was correlated with RANKL production. The frequency of proliferating memory T lymphocytes in response to P. gingivalis serotypes was determined in both periodontitis and healthy subjects. Results T lymphocytes stimulated by K1 or K2‐primed dendritic cells elicited higher levels of RANKL and TRAP+ osteoclasts than cells stimulated with the other serotypes. RANKL positively correlated with RORC2. Whereas periodontitis patients had a higher frequency of memory T lymphocytes responding to K1 or K2, healthy subjects had a higher frequency of memory T lymphocytes responding to K4 or K−. Conclusions P. gingivalis serotypes K1 and K2, but not others, are associated with an increased production of the osteoclastogenesis‐related factor RANKL. This important information suggests that these serotypes could elicit a greater bone resorption in vivo and have a role in the periodontitis pathogenesis.